Advertising : theory and practice - Sandage, C.H.; Fryburger, Vernon; Rotzoli, Kim (Delhi : A.I.T.B.S. Publishers, 2002)
Business
2004-03-28
Keywords: Advertising; Media planning; Budget planning; Advertising organizations